2001
DOI: 10.1080/03079450120078671
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of iron retention in mynahs, doves and rats

Abstract: Iron retention was studied in rats (Rattus norvegicus), doves (Streptopelia d. decaocto) and two species of mynahs (Acridotheres t. tristis and Gracula r. religiosa) fed two different pelleted diets (88.5 and 567.9 mg Fe/kg diet). The doves and rats served as species that are not susceptible to iron storage, whereas the mynahs are known to develop iron overload frequently. The retention was calculated after measuring the uptake and elimination of a single dose of radioactive iron ( 59 Fe) using whole-body coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…This supports the hypothesis that some species may have maximized their efficiency for iron uptake from low iron-content food in their natural habitat and cannot adapt to higher food iron content in captivity (Otten et al, 2001). Experimental studies of mynah birds and starlings suggest that the intestinal absorption of iron in birds is not as tightly regulated as it is in mammals and that susceptible species are unable adequately to down-modulate the uptake of iron to prevent iron storage disease (Ward et al, 1991;Mete et al, 2001Mete et al, , 2003. Mynah birds have greater intestinal uptake of iron compared with chickens and doves.…”
Section: Iron Storage In Birds: Malnutrition Orsupporting
confidence: 55%
See 2 more Smart Citations
“…This supports the hypothesis that some species may have maximized their efficiency for iron uptake from low iron-content food in their natural habitat and cannot adapt to higher food iron content in captivity (Otten et al, 2001). Experimental studies of mynah birds and starlings suggest that the intestinal absorption of iron in birds is not as tightly regulated as it is in mammals and that susceptible species are unable adequately to down-modulate the uptake of iron to prevent iron storage disease (Ward et al, 1991;Mete et al, 2001Mete et al, , 2003. Mynah birds have greater intestinal uptake of iron compared with chickens and doves.…”
Section: Iron Storage In Birds: Malnutrition Orsupporting
confidence: 55%
“…Some bird families, especially Sturnidae, Ramphastidae and Paradisaeidae, may be predisposed due to a specific sensitivity to dietary iron uptake (Lowenstine and Munson, 1999). The pathophysiology of avian iron storage syndromes remains obscure; however, Mete et al (2001Mete et al ( , 2003Mete et al ( , 2005 have shown for mynah birds that the intestinal iron uptake and transfer into circulation is increased compared with species that are not susceptible. Therefore, at least in some avian species, the rate of iron load appears to be influenced by species-specific physiological mechanisms.…”
Section: Iron Storage In Birds: Malnutrition Ormentioning
confidence: 98%
See 1 more Smart Citation
“…Seabirds defecate at foraging sites in viscous, liquid form on the surface layer of the ocean. Iron is generally toxic to birds, and roughly 90% of ingested iron must be excreted (52). Reported iron concentration in seabird feces is 185 ± 9.3 ppm dry weight (53), which is similar to the iron concentration in baleen whale fecal plumes (166.6 ± 155.2 ppm dry weight) (47).…”
Section: Resultsmentioning
confidence: 52%
“…Furthermore, the fruit bats in our study absorbed more iron than doves (Streptopelia d. decaocto; mucosal uptake and transfer 5 3-11%) and depending on treatment, had comparable iron absorption to rats (Wistar; 17-34%) and ISDsusceptible mynahs (Acridotheres t. tristis, Gracula r. religiosa; 23-47%); however, the multispecies study [Mete et al, 2001] used methods inconsistent with this study; thus absorption values may not be directly comparable. While the doves and rats were able to downregulate iron absorption when fed a high iron diet, the iron sensitive mynahs were not.…”
Section: Discussionmentioning
confidence: 73%